(3TQM GdbUjOI GddGejI aiJGQjN NdaGA GdOhdI GdESdGejIs - (3UOQ GdOjf CHh GdMSf Ydj Hf YdGA GdOjf Hf GdYR GdMfajs; (3Ydj Hf YdGA GdOjf Hf GdYR GdMfaj, UOQ GdOjf CHh GdMSfs
(3ChdgG (B:s
(3Chd GdbUjOI bhdg (B: (3CdG CMeO Gddg Gdejgef PG GdYdG hPG Gdedc jDJjg hjfRYg GHJdG Chd GdTQM bhdg GdMeO ddg QH GdYGdejf hHYO agPg ChQGb JTJed Ydi Md QehR GdbUjOI s
(3BNQgG (B:s
(3BNQ GdbUjOI bhdg (B: (3dg GdMeO ai MGdi QNGFi hTOJi aeGdi ShGg ai GdTOGFO ehFdG BNQ GdTQM bhdg hgh dZWG GdMdGFa hGdNdGa , hGdKGfi jSei GdJLfjS GdePjd hGdMeO ddg QH GdYGdejf s
(3Hjf GdbUjOI hGdTQM ebOGQ KdGK hQbGJ HNW eNJda hajgG CTYGQ eJfhYIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs